Identifying genetic hypomethylation and upregulation of toll-like receptors in Kawasaki disease - Huang, Ying-Hsien (Oncotarget, 2017)
Kawasaki disease (KD) is an acute febrile systemic vasculitis that occurs in children and is characterized by elevated levels of proinflammatory cytokines. Toll-like receptors (TLRs) serve as the sensor arm of the innate immune system and induce proinflammatory cytokine expressions. We recruited a total of 18 paired KD patients, before intravenous immunoglobulin (IVIG) and at least 3 weeks after IVIG treatment, 18 healthy controls, and 18 febrile controls. For TLR genes and their cytosine-phosphate-guanine (CpG) markers, we used Affymetrix GeneChip(®) Human Transcriptome Array 2.0 and Illumina HumanMethylation450 BeadChip to evaluate gene expression levels and methylation patterns, respectively. KD patients demonstrated a significantly differential expression of TLR mRNA levels compared to both the healthy and febrile controls, with only TLR 3 and 7 not differing between the KD patients and the controls. After patients underwent IVIG treatment, the TLR mRNA levels, except for TLR3, decreased significantly in KD patients. In contrast, the methylation status of the CpG sites of TLR1, 2, 4, 6, 8, and 9 demonstrated an opposite tendency between the two stages of both the KD samples and the controls. TLRs, particularly TLR1, 2, 4, 6, 8, and 9, may stimulate the immunopathogenesis of KD. These results are among the first to use TLRs to prove that a bacterial inflammatory response may trigger KD.